2016
DOI: 10.1039/c6dt00115g
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor organo-imido polyoxometalates: high transparency, high activity redox-active NLO chromophores

Abstract: We show that polyoxometalates (POMs) are an excellent redox-active acceptor on which to base high performance 2(nd) order non-linear optical (NLO) chromophores. This is demonstrated through three new organoimido-Lindqvist derivatives with HRS β0-values exceeding those of any dipolar organic system with comparable donor, π-system and absorption profile. Thus, organoimido POMs may provide a new generation of high performance, high transparency, and potentially redox-switchable NLO materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 67 publications
2
25
2
Order By: Relevance
“…They are also essential for photodynamic therapy, biological imaging, and the protection of human eyes and optical sensors (by NLO materials with optical limiting effects) from high intensity LASER beams [3,4]. NLO effects arise from the interaction of an applied optical field (usually LASER) with the electronic field created by the oscillation of electrons in a NLO material, generating a new optical field that is altered in frequency, amplitude, phase, or any other physical property [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…They are also essential for photodynamic therapy, biological imaging, and the protection of human eyes and optical sensors (by NLO materials with optical limiting effects) from high intensity LASER beams [3,4]. NLO effects arise from the interaction of an applied optical field (usually LASER) with the electronic field created by the oscillation of electrons in a NLO material, generating a new optical field that is altered in frequency, amplitude, phase, or any other physical property [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is a potential new class of NLO materials with much better transparency/non-linearity trade-offs and reversible electrochemistry than related organic systems. 95…”
Section: Organoimido Derivatives Of Poms: Synthesis and Applicationsmentioning
confidence: 99%
“…Dalton TransactionsFielden et al have proved that polyoxometalates (POMs) can be outstanding redox active acceptors for high-performance second-order nonlinear optical (NLO) chromophores. It is a potential new class of NLO materials with much better transparency/non-linearity trade-offs and reversible electrochemistry than related organic systems 95. In2017, Diego Venegas-Yazigi et al reported the synthesis, electrochemical and photophysical properties of the first Re organometallic hybrid POM [ n Bu 4 N][Mo 6 O 18 NC 6 H 4 -CH 2 -N 3 C 2 H 2 -Re-phen(CO) 3 ] (Scheme 13).…”
mentioning
confidence: 99%
“…The authors attribute the large response to a modulation of the conjugation along the polymer backbone. Al-Yasari et al have characterized donoracceptor organo-imido polyoxometalates with static first hyperpolarizabilities that exceed those of comparable compounds [76]. And Coe et al have investigated the second-order nonlinear optical response of Helquat dyes with large static first hyperpolarizabilities [77].…”
Section: B Post-tfl Experimental Researchmentioning
confidence: 99%